Pengaruh Pemberdayaan Pegawai, Gaya Kepemimpinan, dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai di Sektor Penanggulangan Kebakaran dan Penyelamatan Kecamatan Kramat Jati Jakarta - Muhammad Fahrurriansyah; Anita Maulina (Reformasi Administrasi, 2025)
Job satisfaction is a positive or pleasant emotional condition resulting from an assessment of one's work or work experience. Without employee satisfaction, the organization will not be able to run well. This research discusses and analyzes the influence of employee empowerment, leadership style, and organizational culture on employee job satisfaction in the Fire Management and Rescue Sector, Kramat Jati District. The research method used is a quantitative method by distributing questionnaires with a sample size of 52 respondents from a population of 52 people. Based on the results of research using multiple regression analysis with the help of SPSS 26.0, it shows that employee empowerment has a positive and significant influence with a coefficient of determination (R Square) of 0.924 (92.4%) on employee job satisfaction, leadership style has a positive and significant influence with a coefficient of determination (R Square) of 0.770 (77.0%) on employee job satisfaction, organizational culture has a positive and significant influence with a coefficient of determination (R Square) of 0.676 (6.76%) on employee job satisfaction. The independent variables employee empowerment, leadership style, and organizational culture were jointly tested using the F test, proving to have a positive and significant influence with an F value of 198.626 on employee job satisfaction and the magnitude of the influence was seen from the value and with a coefficient of determination (R Square) value of 0.925 (92.5%).